2022
DOI: 10.3390/ijerph19127108
|View full text |Cite
|
Sign up to set email alerts
|

Healing Process, Pain, and Health-Related Quality of Life in Patients with Venous Leg Ulcers Treated with Fish Collagen Gel: A 12-Week Randomized Single-Center Study

Abstract: The aim of the study was to assess the effectiveness of fish skin collagen and its impact on healing, pain intensity, and quality of life in patients with venous leg ulcers (VLUs). This study included 100 adults with VLUs. Eligible patients were randomized to either tropocollagen gel treatment (group A, n = 47) or placebo alone (group B, n = 45). We applied the gel to the periwound skin for 12 weeks. All groups received standard wound care, including class 2 compression therapy and wound hygiene procedures. We… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 59 publications
1
5
0
Order By: Relevance
“…Regarding the sociodemographic profile, the participants in our sample were mostly woman, aged 60 years or older (considered older people in Brazil), of low income and education, and did not have professional activity. These data are similar to other profiles found in the literature [ 5 , 21 , 22 ]. Authors explained that VU are more common in women, since in this public there is greater overload in the venous network, which presupposes fluid retention and greater difficulties in venous return when compared to men [ 1 ].…”
Section: Discussionsupporting
confidence: 91%
“…Regarding the sociodemographic profile, the participants in our sample were mostly woman, aged 60 years or older (considered older people in Brazil), of low income and education, and did not have professional activity. These data are similar to other profiles found in the literature [ 5 , 21 , 22 ]. Authors explained that VU are more common in women, since in this public there is greater overload in the venous network, which presupposes fluid retention and greater difficulties in venous return when compared to men [ 1 ].…”
Section: Discussionsupporting
confidence: 91%
“…Several studies observed a complete healing rate of VLU of 23–35% after 12 weeks of standard treatment [ 28 , 29 , 30 , 31 , 32 ]. We reached 55.6% completely healed wounds, which indicates support for wound healing compared to standard therapies ( Table 3 ).…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, when we performed the analysis, considering the subcategories of sociodemographic variables, we noticed that this correlation lost strength and statistical significance among participants under 60 years of age. Authors have pointed out that pain is present in most people with VU and is related to local hypoxia triggered by poor circulation in the affected limb, which can lead to impairments in the mobility of the individuals and their willingness to perform homework and social interaction activities [ 24 , 25 ]. It is important to highlight that in other QoL scales used in people with VU, as well as in the SF-36, pain is one of the aspects evaluated individually; this is the case for the Charing Cross Venous Ulcer Questionnaire, Venous Leg Ulcer Quality of Life (VLU-QoL), Sheffield Preference-based Venous Ulcer Questionnaire (SPVU-5D), and the EQ-5D-5L [ 10 ].…”
Section: Discussionmentioning
confidence: 99%